We know that the polynomial has roots of multiplicity 2 at x=-3 and x=2, therefore, it must be of the form:
![Y(x)=P(x)(x+3)^2(x-2)^2.](https://img.qammunity.org/2023/formulas/mathematics/college/up8gyvn2lxbndnprxzgr79g83n781udo7w.png)
Now, we are given that the polynomial has a root at x=-2, we get that:
![P(x)=k(x+2)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/4zh4rcdi7inwtrxl1olsmkxhxqgyug545e.png)
Therefore:
![Y(x)=k(x+2)(x+3)^2(x-2)^2.](https://img.qammunity.org/2023/formulas/mathematics/college/tpfq45wz6isiwlsjvr6fs1e6itjve4z9cv.png)
To determine the value of k we use the fact that the y-intercept is at (0,24):
![Y(0)=24=k(0+2)(0+3)^2(0-2)^2=k\cdot2\cdot9\cdot4=72k.](https://img.qammunity.org/2023/formulas/mathematics/college/iw85zx79vkcpcgk93zkajpbpiqr5iq9yk3.png)
Solving the above equation for k, we get:
![k=(24)/(72)=(1)/(3)\text{.}](https://img.qammunity.org/2023/formulas/mathematics/college/npfhabggr27b2c1yq9rwdi3t3oeyifvy1z.png)
Finally, substituting the value of k, we get that:
![Y(x)=(1)/(3)(x+2)(x+3)^2(x-2)^2.](https://img.qammunity.org/2023/formulas/mathematics/college/k4eq9qt5quhdclfmyliqox8sdn1xftcxbd.png)
Answer:
![(1)/(3)(x+2)(x+3)^2(x-2)^2.](https://img.qammunity.org/2023/formulas/mathematics/college/r31y8vfews7n06hrwj2x8r2ef7vffgybyk.png)